Introduction to statistical quality control - Montgomery, Douglas C. (Wiley, 1996)
This book explores the modern use of statistical methods in quality control and improvement. It provides comprehensive coverage of the subject from basic principles to state-of-the-art concepts and applications. While statistical techniques are emphasized throughout, the book has a strong engineering and management orientation, showing how modern engineers use quality control today.